Design and development of a modular vibration test rig for combination types of fault in rotating machinery health diagnosis - Silahuddin, S. M.; Abang Mohamad, Aizuddin; Shahrol, Mohamaddan; Syed Tarmizi, Syed Shazali; Mohamad Syazwan Zafwan, Mohamad Suffian; Adrus, Mohamad Tazuddin; Azfar Satari, Abdullah (Universiti Malaysia Pahang, 2019)
As a basis to real application of rotating machineries operation, a test rig imitating the operation is designed for the research environment. The purpose of this study is to design a modular test rig which is able to facilitate different fault component combinations and evaluate the deformation pattern of the fabricated test rig. Rotating machineries face the probability of having simultaneous different faults and the study of this condition is limited. The designed test rig could be arranged into multiple configurations by adding or excluding desired components due to its modularity. This will be useful to study the response of each component during operation as well as the response of combinations of fault components. Included in this study is the analysis of the design where the maximum possible operating condition at 60Hz speed was considered. The final test rig design was included as well as the experimental displacement data results of the fabricated test rig showing 17.5% measurements to exceed 1mm displacement. This test rig is beneficial for understanding the vibrational behavior of components and is designed for the educational environment.